Family Endowment Reconsidered - Reddaway, W. B. (Review of Economic Studies, 1938)
Family Endowment Reconsidered Get access W. B. Reddaway W. B. Reddaway Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 2, February 1938, Pages 123–131, https://doi.org/10.2307/2967526 Published: 01 February 1938